A STUDY ON COMPETENCY MAPPING OF EMPLOYEES WITH REFERENCE TO MURUGAPPAN AND COMPANY - A.Tejeswari, Dr.T.V.Ambuli (International Journal of Research Science and Management, 2016)
Human resource management is a process of bringing people and organizations together so that the goals of each other are met. Over the years, there is a change in the nature of jobs, which calls for future skill mapping through proper HRM initiatives. Indian organizations are also witnessing such a change which brings about the need for a multi skill development There arises the need of competency mapping. Competency mapping identifies an individual’s strengths and weaknesses in order to help them better understand themselves and to show them where career employees with reference to Murugappan and company. Research design adopted for the study is descriptive study with a sample size of 102. Tools used in the present study are percentage analysis, chi-square, coorelation and regression analysis.From the study it is found that there is no association between work experience and high emotional strength. •So Use of occasional skill tests within the department could help the employees to keep a track of where exactly they stand and thus would help them put more development efforts need to be directed. The present study is about competency mapping of authentic ratings when asked to.